La transversalidad del currículo y el proceso de enseñanza aprendizaje - Pucha Chiluiza, Jeny Natalia (2018)
The present research project was developed to determine the importance of transversality in the curriculum as an instrument for integrating the areas of knowledge into the learning process to promote education integral. The problem addressed in this research was the lack of articulation between the scientific and technical contents taught in the educational institution and the characteristics and problems of the specific social and cultural context, thus affecting the integral development of the students. For this purpose, a methodology of qualitative approach was used, supported in the inductive and analytical-synthetic methods, as well as the bibliographic-documentary and field design, which allowed to determine the current situation of inclusion of the transversal axes in the Institution. The theoretical and practical contributions of the research were the scientific and technical bases compiled, which allowed to argue the importance of developing transversal axes in education, system in the same way, the practical contribution of the research settled in the diagnosis of the current situation of knowledge the use of the transversal axes of the curriculum by the teachers of the institution. The impact of the project was at an educational level aimed at achieving a quality of comprehensive education that would form students in all dimensions of their development, at the social level, by the educational approach that is proposed to achieve with the integration of the axes curriculum transversal. The results obtained in the research allowed to establish the deficiencies and limitations that the teachers have to incorporate the transversal axes in their educational practices, framed in the lack of knowledge and commitment for the Constant of these axes in the teaching-learning process, as well as the scarce training and the lack of suitable strategies that allow the student to achieve meaningful learning.